2013
DOI: 10.1080/14786419.2013.821123
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial and antimalarial activities of crude extract, fractions and 4-nerolidylcathecol from the aerial parts ofPiper umbellataL. (Piperaceae)

Abstract: Presently, natural products, such as Piper umbellata L. (Piperaceae), have been evaluated as sources of antimicrobial agents with efficacies against microorganisms. The in vitro antimicrobial activity was performed by broth micro-dilution susceptibility assay, according to the protocols of the National Committee for Clinical Laboratory Standards, and described the antibacterial and antifungal activities of crude ethanolic extract and fractions obtained by partitions sequentially among water-methanol, methylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…4-nerolidylcatechol is a semi synthetic derivative of catechol known for its antimalarial activity. (Bagatela et al, 2013;Pinto et al, 2009;Rocha et al, 2011;Silva Lima et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4-nerolidylcatechol is a semi synthetic derivative of catechol known for its antimalarial activity. (Bagatela et al, 2013;Pinto et al, 2009;Rocha et al, 2011;Silva Lima et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The 4-Nerolidylcatechol has been studied for strong antimalarial property including antioxidant and anti-inflammatory activities as per the data of previous studies. In a recent investigation, new derivatives of 4-NC were synthesized and experimentally validated for the inhibition of Plasmodium (Bagatela et al, 2013;Pinto et al, 2009;Rocha et al, 2011;Silva Lima et al, 2012 …”
Section: Introductionmentioning
confidence: 99%
“…The isolation of 4-nerolidylcatechol was performed by column chromatography and identified by nuclear magnetic resonance (NMR) through 13 C NMR and 1 H NMR analyses (Kijjoa et al, 1980;Bagatela et al, 2013) (Figure 1). …”
Section: Isolation and Identification Of 4-nerolidylcatecholmentioning
confidence: 99%
“…(Piperaceae) demonstrated the presence of several chemical constituents, such as β-stigmasterol, β-sitosterol, and campesterol (Perazzo et al, 2005;Pino et al, 2005;Baldoqui et al, 2009;Bagatela et al, 2013). Plants containing these bioactive molecules have previously demonstrated a significant anti-inflammatory activity (Navarro et al, 2001).…”
Section: Phytochemical Constituents Of P Umbellata Lmentioning
confidence: 99%
“…The family Piperaceae is composed of four major genera and nearly 4000 species, and they are reputed in various systems of medicine for their numerous medicinal properties, such as the Indian Ayurvedic system of medicine and folklore medicine of Latin America (Bagatela et al 2013;Lemos et al 2013;de Queiroz et al 2014;Sarwar et al 2015). Black pepper is the dried ripe fruit of Piper nigrum L., previous studies have revealed its chemical compositions (amide alkaloids, terpenoids, multimeric alkaloids and volatile oil) and activities (immunomodulatory, stimulatory, larvicidal, anti-inflammatory, antioxidant, antifertility, antiulcer, antifungal, antibacterial and anticholinesterase activities) (Ingkaninan et al 2003;Meghwal & Goswami 2013;Santiago et al 2015).…”
mentioning
confidence: 99%